Abuse Characteristics and the Concordance of Child Protective Service Determinations and Adolescent Self-Reports of Abuse. (August 2018) - Kobulsky, Julia M.; Kepple, Nancy Jo; Jedwab, Merav
This study examines the concordance of abuse self-reported by adolescents at 18 years and child protective service (CPS) determinations and how abuse characteristics predict concordance. It includes 819 youths participating in 18-year interviews of the Longitudinal Study of Child Abuse and Neglect (LONGSCAN). Cross-tabulations revealed low correspondence between self-reports and CPS determinations of physical, sexual, and emotional abuse. Logistic regression identified that among youths with CPS physical abuse determinations, White race, chronicity, and co-occurring neglect were positively associated with corresponding self-reports. Co-occurring CPS-determined emotional abuse was more concordant with self-reports. More frequent self-reported physical abuse was associated with corresponding CPS determinations. Self-reports of childhood emotional abuse and perpetration by nonparental family/other household members were positively associated with corresponding CPS determinations. CPS determination concordance also varied significantly by LONGSCAN site. Results demonstrate differences in abuse characteristics captured by CPS data and youth self-report, which may impact research findings on abuse correlates.